Fabrication of Al-Doped TiO2 Visible-Light Photocatalyst for Low-Concentration Mercury Removal - Cheng-Yen Tsai; Tien-Ho Kuo; Hsing-Cheng Hsi (International Journal of Photoenergy)
High-quality Al-doped TiO2 visible-light photocatalyst was prepared via a single-step direct combination of vaporized Ti, Al, and O2 using a 6 kW thermal plasma system. Results showed that the formed Al-doped TiO2 nanoparticles were a mixture of anatase and rutile phase and had a size between 10 and 105 nm. The absorption spectra of the nanoparticles shifted towards the visible light regions, depending on the Al2O3 addition. Ti4+ and Ti3+ coexisted in the synthesized Al-doped TiO2; the Ti3+ concentration, however, increased with increasing Al2O3 addition due to Al/Ti substitution that caused the occurrence of oxygen vacancy. Hg0 breakthrough tests revealed that the nanoparticles had an appreciable Hg0 removal under visible-light irradiation. Nevertheless, moisture reduced Hg removal by the nanoparticles, especially when visible-light irradiation was applied, suggesting that the competitive adsorption between H2O and Hg species on the active sites of TiO2 surface occurred.